Numerical simulations of non-stationary distributions of electrochemical potentials in SOFC. Issue 6 (7th August 2017) - Muramatsu, Mayu; Yashiro, Keiji; Kawada, Tatsuya; Tarada, Kenjiro
Abstract : Purpose: The purpose of this study is to develop a simulation method to calculate non-stationary distributions of the chemical potential of oxygen in a solid oxide fuel cell (SOFC) under operation. Design/methodology/approach: The initial-boundary value problem was appropriately formulated and the appropriate boundary conditions were implemented so that the problem of non-stationary behavior of SOFC can be solved in accordance with actual operational and typical experimental conditions. The dependencies of the material properties on the temperature and partial pressure of oxygen were also elaborately introduced to realize actual material responses. The capability of the proposed simulation method was demonstrated under arbitrary operating conditions. Findings: The steady state calculated with the open circuit voltage condition was conformable with the analytical solution. In addition, the transient states of the spatial distributions of potentials and currents under the voltage- and current-controlled conditions were successfully differentiated, even though they eventually became the same steady state. Furthermore, the effects of dense materials assumed for interconnects and current collectors were found to not be influential. It is thus safe to conclude that the proposed method enables us to simulate any type of transient simulations regardless of controlling conditions. Practical implications: Although only uniaxial models were tested in the numerical examples in this paper, the proposed method is applicable for arbitrary shapes of SOFC cells. Originality/value: The value of this paper is that adequate numerical simulations by the proposed method properly captured the electrochemical transient transport phenomena in SOFC under various operational conditions, and that the applicability was confirmed by some numerical examples.